A higher preconceptional paternal body mass index influences fertilization rate and preimplantation embryo development. (25th November 2021) - Hoek, Jeffrey; Schoenmakers, Sam; van Duijn, Linette; Willemsen, Sten P.; van Marion, Eva S.; Laven, Joop S. E.; Baart, Esther B.; Steegers‐Theunissen, Régine P. M.
Abstract: Background: Obesity is a worldwide problem affecting the health of millions of people throughout the life course. Studies reveal that obesity impairs sperm parameters and epigenetics, potentially influencing embryonic development. Objective: To investigate the association between preconceptional paternal body mass index (BMI) and embryo morphokinetics using a time‐lapse incubator and in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) outcomes. Materials and methods: Participants were recruited from a tertiary hospital in this prospective periconceptional cohort study. A total of 211 men were included: 86 with normal weight (BMI < 25.0), 94 overweight (BMI 25–29.9), and 41 obese (BMI ≥ 30). These men were part of a couple that underwent IVF/ICSI treatment with ejaculated sperm after which 757 embryos were cultured in a time‐lapse incubator. The main outcome parameters consisted of fertilization rate, embryo developmental morphokinetics, embryo quality assessed by a time‐lapse prediction algorithm (KIDScore), and live birth rate. Results: A higher paternal BMI was associated with faster development of the preimplantation embryo, especially during the first cleavage divisions ( t 2: −0.11 h ( p = 0.05) and t 3: −0.19 h ( p = 0.01)). Embryo quality using the KIDScore was not altered. The linear regression analysis, after adjustment for confounders (paternal age, ethnicity, smoking, alcohol use, education, total motile sperm count, and maternal age and BMI), showed an inverse association between paternal BMI and fertilization rate (effect estimate: −0.01 ( p = 0.002)), but not with the live birth rate. Discussion and conclusion: Our data demonstrate that a higher preconceptional paternal BMI is associated with a reduced fertilization rate in IVF/ICSI treatment. Our findings underline the importance of a healthy paternal weight during the preconception period.